2005
DOI: 10.1123/japa.13.4.434
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Osteoarthritis and Adherence to Exercise: A Review of the Literature

Abstract: Osteoarthritis (OA) is a chronic disease that disables many aging adults. People with OA are often asked to adhere to prescribed exercise regimens that must be undertaken in the presence of pain and other disease-related symptoms. We conducted a review of literature that focused on what is known about exercise adherence and the factors that infl uence exercise adherence among people with OA. Results revealed multiple determinants of exercise adherence; however, these determinants have not been carefully studie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
81
0
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(88 citation statements)
references
References 102 publications
5
81
0
1
Order By: Relevance
“…58 Unfortunately, up to 80% of adults with arthritis do not adhere to these recommendations. 57,59,60 Low rates of adherence illustrate the restrictions on physical activity participation that exist among people with arthritis. Yet physical activity adherence among adults with various types of arthritis, including OA, has been shown to reduce pain, increase physical function, and improve falls efficacy.…”
Section: The Relationship Of Balance and Walking Limitations To Incrementioning
confidence: 99%
See 1 more Smart Citation
“…58 Unfortunately, up to 80% of adults with arthritis do not adhere to these recommendations. 57,59,60 Low rates of adherence illustrate the restrictions on physical activity participation that exist among people with arthritis. Yet physical activity adherence among adults with various types of arthritis, including OA, has been shown to reduce pain, increase physical function, and improve falls efficacy.…”
Section: The Relationship Of Balance and Walking Limitations To Incrementioning
confidence: 99%
“…64 Investigating processes important for regular participation in physical activity is therefore crucial for understanding how to improve poor adherence among all adults with arthritis. 59,60 Ideally, such research should be theory driven in order, first, to identify reliable determinants of adherence and, second, to use theory as the guiding framework from which intervention strategies can be designed and implemented to positively affect determinants of adherence. [64][65][66] Although not extensive, there is evidence from research reviews and studies that both environmental contextual and personal contextual factors (i.e., ICF factors; see Figure 1) are associated with physical activity adherence in people with arthritis.…”
Section: The Relationship Of Balance and Walking Limitations To Incrementioning
confidence: 99%
“…33,193,194 Most studies are short term, use limited measures of adherence and standardised exercise programmes. 205 Adherence, independent of exercise type, may be an important factor in the success of exercise interventions. There is evidence that better adherence to exercise improves pain relief 192 and disability 205 and that the addition of booster sessions may be helpful in maintaining positive effects on pain and function.…”
Section: Introductionmentioning
confidence: 99%
“…205 Adherence, independent of exercise type, may be an important factor in the success of exercise interventions. There is evidence that better adherence to exercise improves pain relief 192 and disability 205 and that the addition of booster sessions may be helpful in maintaining positive effects on pain and function. 204 A UK consensus 32 identified adherence and tailoring of exercise to individuals as important research topics.…”
Section: Introductionmentioning
confidence: 99%
“…Long-term exercise adherence is important in order to help reduce the likelihood of OA-related disability (Marks and Allegrante 2005). A study among adults with OA, RA and other types of arthritis found participants wanted arthritis-specific programs and many felt there was a lack of available aqua-based exercise programs (Wilcox, Der Ananian et al 2006).…”
mentioning
confidence: 99%